Tetrazolium salts and formazan products in Cell Biology: Viability assessment, fluorescence imaging, and labeling perspectives - Stockert Cossu, Juan Carlos (2018)
For many years various tetrazolium salts and their formazan products have been employed in histochemistry and for assessing cell viability. For the latter application, the most widely used are 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT), and 5-cyano-2,3-di-(p-tolyl)-tetrazolium chloride (CTC) for viability assays of eukaryotic cells and bacteria, respectively. In these cases, the nicotinamide-adenine-dinucleotide (NAD(P)H) coenzyme and dehydrogenases from metabolically active cells reduce tetrazolium salts to strongly colored and lipophilic formazan products, which are then quantified by absorbance (MTT) or fluorescence (CTC). More recently, certain sulfonated tetrazolium, which give rise to water-soluble formazans, have also proved useful for cytotoxicity assays. We describe several aspects of the application of tetrazolium salts and formazans in biomedical cell biology research, mainly regarding formazan-based colorimetric assays, cellular reduction of MTT, and localization and fluorescence of the MTT formazan in lipidic cell structures. In addition, some pharmacological and labeling perspectives of these compounds are also described.